Analysis of Impact of Crime Victims’ Consent on the Criminal and Civil Liability with a look at Iran's legislative process - Abolfazl Elyasinia; Teybeh Arefnia (مطالعات فقه و حقوق اسلامی, 2021)
The victim’s consent to commit a crime against himself/herself does not affect the criminal and civil liability of the offender. Because enforcing the laws and giving sentences are not to serve the individual's interests. Rather, it is for the establishment and maintenance of public order and the security of society. Therefore, due to the legal rules and legislation, victim’s satisfaction carries no legal value and validity and is not considered as a justified cause for the crime. In some cases, however, due to its benefits and social necessity and acceptance, and sometimes due to the character and nature of the crime committed, the legislator has regarded the victim's dissatisfaction as one of the essential elements that form the crime. Hence, with the victim’s consent, the criminal nature of the offense is altered, thereby it prevents the criminal and civil liability from being established. This article attempts to analyze and compare the impact of the victim's consent on criminal and civil liability for crimes against people, such as medical errors, etc. from the perspective of the legislative process and Islamic jurisdiction.